Case report of secondary hypertension due to renal artery stenosis in young patient (Medical Journal of Indonesia, 2014)
Secondary hypertension is rare to occur, but should become suspicion in young age. Secondary hypertension must be appropriately diagnosed and treated. Renal artery stenosis is one of many causes of secondary hypertension. The aim of this case report is to describe diagnosis, pathophysiology and management of secondary hypertension due to renal artery stenosis in young patient. A 17 year old man with symptom of shortness of breath was diagnosed with hypertension stage 3 on his medical examination at Pasar Rebo Hospital, Jakarta. Abdominal CT scan examination revealed bilateral renal artery stenosis. Percutaneous transluminal angiography (PTA) of left renal artery was performed at National Cardiovascular Centre Harapan Kita. Stent was placed succesfully and the blood pressure was normalized.